Paying the head of the dead: the role of kin in the yung ceremony among Sentani peoples in Jayapura Papua Indonesia - Fredrik Sokoy; Usman Idris (Cogent Arts & Humanities)
The yung ceremony is a ceremony to ‘pay the head’ of the dead in the culture of the Sentani people which is still maintained today. This paper will analyze the role of relatives in the process of ‘paying the head’ of the dead among Sentani people. The research approach used is descriptive qualitative with ethnographic approach. The data collection techniques used are observations, interviews, and literature studies. Research results show that the ritual of paying the head of the dead called yung is a cultural tradition of the Sentani people which is included in the life cycle rites. The yung tradition is very important since it determines social status and has several functions (religious, economic, and socio-political functions), involves the elements of traditional leadership (ondofolo, koselo, or clan leaders), and strengthening bonds of solidarity with the involved kinship groups. The role of the conjugal and affinal relative groups on the male and the female side participating in all activities related to the yung ceremony process, in which the relatives groups of the male side (husband) have the obligation and responsibility to collect the harta kepala (‘head’ property), while the conjugal and affinal relatives group of the woman (wife) is entitled to receive the head payment property stipulated in their customary rules.